Collaborative Online Learning and Art Education - Silva, Vitor (2017)
This paper presents a case study carried out with elementary school students analyzing the collaborative activities developed in a community created in the Edmodo digital platform. The research development technique was positioned in the interpretative and qualitative paradigm using the content analysis of the discussions and artifacts created. The results show the level of collaboration of the group and the influence of some tools and methods, making evident the need to do other studies on analogous communities dedicated to artistic education in the early age.